REFORMULATING DRACULA IN THE EARLY 21ST CENTURY: GENRE ANALYSIS OF 24 VAMPIRE FILMS - Nofiyanti Fuanda (Rubikon : Journal of Transnational American Studies, 2016)
The vampire is a phenomenon in western literature and culture. As many literary works featuring vampire are produced every year and continue to interest of the audiences, the creature becomes even embedded in the heart of not only western people, but also most people in the world. Currently, the researches on the creature either as a part of the myth or a character in literary works is so booming. They conclude that there is transformation of vampire both in myth and literary work. The research on literary works mostly generalizes vampire and Dracula as similar terms referring to blood sucker in general. In fact, those two terms actually refer to different signifieds. Therefore, this research aims to discuss specifically the development of literary works, especially films featuring the Dracula character since Stoker’s story is still adapted in the current era. The discussion focuses on the conventions and inventions of Dracula films in the early twenty first century and how those new formulas are related to the social background. This research is qualitative research and data are collected from the library. In addition, the basic theory used is genre analysis which situates texts within textual and social contexts. In the field of American Studies, such analysis is relevant to McDowell’s theory of “past, present and future” which supports interdisciplinary studies of time development.As the finding of the research on twenty four films produced during 2000 to 2014 the researcher concludes that most of them mix the elements of some genres. There are eleven pure horror Dracula films, eight horror action, two horror drama, one horror adventure, one horror sci-fi, and one horror romance. Furthermore, the researcher found five formula inventions including: 1. the shifting themes which include the emergence of science and the blurring of sexuality; 2. the variation of the stereotypical characters which includes the turn of the villain into hero and the challenge of women as heroes; 3. the changing motive; 4. the variation of setting, and 5. the replacement of properties. In the further analysis, the development of the formulas is certainly the result of the mixing genres, and also the response to two major issues flourishes in today’s era such as the issue of modernity and rationality and the phenomenon of ‘New Women’ and ‘Now Women.’Keywords: vampire, Dracula, formula, convention, invention